The Effect Of Using Introductory And Patient Questions On Developing Expressive Performance Among Middle School Students - K. Jawad, Intisar (Opción, 2019)
Education is an essential force in directing the current of change and taking advantage of the renewed and enlightened means of knowledge in the service of humanity in our time so it aims to develop the individual with a comprehen- sive and integrated development and prepare him for life by providing him with knowledge, skills and information and employing and developing them in order to achieve the educational goals that he drew in light of many studies and researches I found that there is weakness in verbal, written and verbal expression at all levels of education, which creates in them a sense of fear and confusion, and separates them from the language they learn practically, tech- nically and skillfully while they use the language. The Arabic language and its implications and derivations are also considered to be one of the richest and most abundant languages, and the broadest is what goes under the sense or goes into mind to achieve language sciences, good laws and organization of ideas, and depicting its imagination through the use of expression, which gen- erates educational and learning benefits as it develops the ability of students to Noticing things with an artistic sense, and analyzing ideas in a way. The use of classroom questions in light of the school curriculum of the Arabic lan- guage and the method in a meaningful and effective way that helps to develop self-confidence through the students ’taste of success taste when answering the teacher’s various and purposeful questions. The school should provide more opportunities for students to know their abilities for their sense of educational success and the learner sees the researcher there are types Different questions that reveal the students ’abilities towards learning and learning understand- ing in light of the diversity of questions. The researcher used an expressive test of expressive performance to apply to three groups of students, the first is an experimental one, with which the introductory questions were used, and the second also a pilot that used the sounding and the third questions, a traditional one that was used with them, and the number of groups was three. The research goal: - The current re- search aims to know the effect of using introductory and patient questions on developing expressive performance among middle school students